ANALYTICAL MODEL FOR LATHE TOOL DISPLACEMENTS CALCULUS IN THE MANUFACTURING P ROCESS - Catălin ROŞU; Cosmin - Mihai MIRIŢOIU; Vâlcu ROŞCA; Alexandru STANIMIR; Marius Zamfirache (Fiabilitate şi Durabilitate)
In this paper, we present an analytical model for lathe tools displacements calculus in the manufacturing process. We will present step by step the methodology for the displacements calculus and in the end we will insert these relations in a program for automatic calculus and we extract the conclusions. There is taken into account only the effects of the bending moments (because these insert the highest displacements). The simplifying assumptions and the calculus relations for the displacements (linea r and angular ones) are presented in an original way.